Effect of different Additives on Bale Silage Quality of Maize Fodder - Khanday, Zahid Bashir (Indian Journal of Animal Nutrition, 2021)
The present study was conducted to evaluate the effect of different additives on the bale silage quality of maize fodder. An experiment was conducted with four different treatments of maize fodder before bailing them. These treatments consisted of; without additive (MF0), Lactobacillus casei @ 106 CFU/g (NCDC-17) of fresh fodder (MFLAB), Silotan, a commercial product @15ml/100 Kg of fresh maize fodder (MFST) and Formaldehyde @0.5% of fresh maize fodder (MFFA) as silage additives. The bale silage of four such treatments MF0, MFLAB, MFST and MFFA, in replications (3*9 treatments) was prepared by using a high power 100 kg bailing machine. Each treatment was evaluated after 60 days of ensiling in terms of quality parameters, chemical composition, fermentation characteristics, microbial (LAB) counts and In vitro DM degradability. The evaluation of bale silage revealed a significant increase (p<0.001) in pH and decrease (p<0.001) in ammonia nitrogen was observed in MFFA. There was no significant effect on DM, CP, EE and ADF contents of any treatment, however a significant increase (p<0.001) in WSC was observed in MFFA, with a decrease (p<0.001) in WSC of MFLAB. The TVFAs were significantly increased (p<0.001) in MFLAB and MFST, with a decrease (p<0.001) in MFFA. There was a significant decrease (p<0.001) in Acetate content of MFFA while a significant reduction (p<0.001) in Butyrate was observed in MFST and MFFA. There was a significant decrease (p<0.001) in Lactic Acid content of MFFA. In vitro DM degradability was significantly increased (p<0.05) in MFLAB. There was no prominent effect in methane (ml/g DM) production in any of the treatments. The microbial counts were found significantly increased (p<0.05) in MFLAB, with a decrease (p<0.05) on MFFA, while yeast counts were significantly decreased (p<0.05) in MFST with increase in MFFA. It was concluded that Silotan or MFLAB can be used to improve the quality of bale silage.